PENGARUH FINANCIAL ATTITUDE, FINANCIAL KNOWLEDGE, DAN FINANCIAL LITERACY TERHADAP FINANCIAL BEHAVIOR PADA MAHASISWA UNIVERSITAS BHAYANGKARA JAKARTA RAYA KAMPUS BEKASI - Miranda Tri Setyawati; Wirawan Widjanarko; Franciscus Dwikotjo Sri Sumantyo (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the influence of Financial Attitude, Financial Knowledge, and Financial Literacy on Financial Behavior among students of the Management Study Program, Faculty of Economics and Business, Universitas Bhayangkara Jakarta Raya, Bekasi Campus. This research employed a quantitative approach with a sample of 78 respondents selected through simple random sampling. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method with SmartPLS 3.0 software. The results indicate that Financial Attitude does not have a significant effect on Financial Behavior, while Financial Knowledge and Financial Literacy have a positive and significant effect on Financial Behavior. The R-Square value of 0.713 indicates that Financial Attitude, Financial Knowledge, and Financial Literacy explain 71.3% of the variance in Financial Behavior, while the remaining percentage is influenced by other factors outside this study. Therefore, Financial Knowledge and Financial Literacy are important factors in shaping students' financial behavior